2016
DOI: 10.1016/j.atherosclerosis.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α regulates triggering receptor expressed on myeloid cells-1-dependent matrix metalloproteinases in the carotid plaques of symptomatic patients with carotid stenosis

Abstract: Objective To determine the relationship between increased triggering receptor expressed on myeloid cells (TREM)-1 and plaque stability in atherosclerotic carotid stenosis. Methods The mRNA transcripts and protein for TREM-1, MMP-1, MMP-9, collagen type I (COL1A1) and collagen type III (COL3A1) were analyzed by qPCR and immunofluorescence in both tissues and VSMCs isolated from atherosclerotic carotid plaques of symptomatic and asymptomatic patients with carotid stenosis. Results The TREM-1, MMP-1 and MMP-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 44 publications
1
66
0
1
Order By: Relevance
“…Inflammation plays a crucial role in the pathogenesis of plaque development and progression involving mediators such as triggering receptor expressed on myeloid cells 1 (TREM-1), toll-like receptor 4 (TLR4), and cytokines such as IL-6, TNF-α, IL-1β, and IFN-γ, and macrophages [104105] (Figure 3). Low intraplaque VDR expression, the prevalence of VDR expression in M1 compared to M2 macrophages, and increased VDR expression in M1 macrophages incubated with 1,25(OH) 2 D 3 with suppression of TLR4 expression suggest that low intraplaque VDR expression predicts an adverse cardiovascular event in patients with carotid stenosis.…”
Section: Vascular Diseasementioning
confidence: 99%
“…Inflammation plays a crucial role in the pathogenesis of plaque development and progression involving mediators such as triggering receptor expressed on myeloid cells 1 (TREM-1), toll-like receptor 4 (TLR4), and cytokines such as IL-6, TNF-α, IL-1β, and IFN-γ, and macrophages [104105] (Figure 3). Low intraplaque VDR expression, the prevalence of VDR expression in M1 compared to M2 macrophages, and increased VDR expression in M1 macrophages incubated with 1,25(OH) 2 D 3 with suppression of TLR4 expression suggest that low intraplaque VDR expression predicts an adverse cardiovascular event in patients with carotid stenosis.…”
Section: Vascular Diseasementioning
confidence: 99%
“…Further, increased TREM-1 expression is associated with unstable plaque and plaque vulnerability. This suggests that dyslipidemia enhances the inflammation in plaque through increased surface expression of TREM-1 leading to increased monocytes homing, production of pro-atherogenic or pro-inflammatory cytokines, and foam cell formation, and thus enhanced the plaque vulnerability (Rai et al 2016;Rao et al 2016a;Zysset et al 2016) (Figures 2 and 3). Increased expression of TREM-1 on matured dendritic cells has been correlated with plaque instability (Rai et al 2016), and DCs and activated T cells have been (Figures 2 and 3).…”
Section: Oxidized Low-density Lipoprotein (Oxldl)mentioning
confidence: 99%
“…Increased MMP activity is associated with plaque vulnerability and blocking MMPs may be a novel strategy and a promising target for stabilizing vulnerable plaques in patients with carotid stenosis (Rao, et al 2014). Further, the TREM-1 (Rao et al 2016a) and TLR4 (Gargiulo et al 2015) mediated regulation of MMPs via TNF-α in carotid plaque vulnerability, and the role of TREM-1, HMGB-1 and RAGE axis in inflammation has been discussed (Thankam et al 2016) suggesting the association of these mediators in inflammation mediated plaque vulnerability.…”
Section: High Mobility Group Boxmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-density lipoprotein (LDL) plays a significant role in atheroma formation and atherosclerosis, causing plaque formation (Falk 2006), but studies found no significant relationship between total cholesterol and LDL for plaque formation, however it was found that LDL is a significant risk factor and predictor of SCD in the short term (<2yr) but not for the long term (>2ys) (Benchimol et al 2000). Preventing acute ischemia due to plaque rupture using strategies involving plaque stabilization is an evolving area of research (Jia et al 2006Rao et al 2014;Rao et al 2015;Rao et al 2016) (Figure 1). …”
Section: Prevention and Treatmentmentioning
confidence: 99%